Soil enzymes illustrate the effects of alder nitrogen fixation on soil carbon processes in arctic and boreal ecosystems - Calvin B. Heslop; Roger W. Ruess; Knut Kielland; M. Syndonia Bret‐Harte (Ecosphere, 2021)
Abstract As tall shrubs increase in extent and abundance in response to a changing climate, they have the potential to substantially alter Arctic and boreal ecosystem nutrient cycling and carbon (C) balance. Siberian alder (Alnus viridis ssp. fruticosa), a nitrogen (N) fixing shrub, is among the species responding to climate warming in both the Arctic and boreal forests. By relieving N limitation of microbial activity, alder‐fixed N has the potential to increase decomposition of labile soil C. Simultaneously, it may also decrease decomposition of recalcitrant soil C by downregulating microbial N mining. The microbial response to N additions is influenced by differences in the soil organic matter (SOM) chemistry and could ultimately determine whether alder N additions result in a net sink or source of C to the atmosphere. We measured the activities of three extracellular enzymes in bulk organic soils under and away from alder canopies in stands differing in SOM chemistry in both the arctic and boreal forest regions of Alaska, USA. In the Arctic, samples taken from under alder had higher activities of both recalcitrant and labile C‐degrading enzymes than samples taken away, regardless of SOM chemistry. In the boreal forest, enzyme activities did not differ with alder proximity nor stand SOM chemistry, possibly due to long legacies of alder N inputs in these stands. As arctic and boreal forest ecosystems experience shifts in the distribution and abundance of this N‐fixing shrub, alders' influence on soil decomposition could have significant consequences for high latitude soil C budgets.